Notes on the first record in Italy of Rhagoletis completa Cresson (Diptera Tephritidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The nearctic tephritid Rhagoletis completa Cresson is reported for the first time in Italy (Veneto and Friuli Venezia-Giulia). During the summer of 1991, the species was found in walnut orchards of various localities. In some orchards the level of infestation of fruits at harvest was more than 50%. The species is economically important in U.S.A. and especially in California where its biology and behaviour have been well studied and the control methods have been recently improved. Some notes on these subjects are reported here due to the potential injuriousness of R. completa in Italy.
Keywords: walnut; Tephritidae; distribution